Analog design and simulation using OrCAD Capture and PSpice - Fitzpatrick, Dennis (Reader in Biomedical engineering) (Oxford ; Waltham, MA : Newnes, 2012)
Anyone involved in circuit design that needs the practical know-how it takes to design a successful circuit or product, will find this practical guide to using Capture-PSpice (written by a former Cadence PSpice expert for Europe) an essential book. The text delivers step-by-step guidance on using Capture-PSpice to help professionals produce reliable, effective designs. Readers will learn how to get up and running quickly and efficiently with industry standard software and in sufficient detail to enable building upon personal experience to avoid common errors and pit-falls. This book is of great benefit to professional electronics design engineers, advanced amateur electronics designers, electronic engineering students and academic staff looking for a book with a real-world design outlook. Provides both a comprehensive user guide, and a detailed overview of simulation Each chapter has worked and ready to try sample designs and provides a wide range of to-do exercises Core skills are developed using a running case study circuit Covers Capture and PSpice together for the first time.
Chapter 1. Getting Started -- Chapter 2. DC Bias Point Analysis -- Chapter 3. DC Analysis -- Chapter 4. AC Analysis -- Chapter 5. Parametric Sweep -- Chapter 6. Stimulus Editor -- Chapter 7. Transient Analysis -- Chapter 8. Convergence Problems and Error Messages -- Chapter 9. Transformers -- Chapter 10. Monte Carlo Analysis -- Chapter 11. Worst Case Analysis -- Chapter 12. Performance Analysis -- Chapter 13. Analog Behavioral Models -- Chapter 14. Noise Analysis -- Chapter 15. Temperature Analysis -- Chapter 16. Adding and Creating PSpice Models -- Chapter 17. Transmission Lines -- Chapter 18. Digital Simulation -- Chapter 19. Mixed Simulation -- Chapter 20. Creating Hierarchical Designs -- Chapter 21. Magnetic Parts Editor -- Chapter 22. Test Benches -- Appendix. PSpice Measurement Definitions.
Keywords: OrCAD SDT; PSpice; PSpice; OrCAD SDT; OrCAD SDT; PSpice; Electronic circuit design; Electronic circuits -- Computer simulation; Electronic circuit design; Electronic circuits -- Computer simulation